2004
DOI: 10.1096/fj.03-0453com
|View full text |Cite
|
Sign up to set email alerts
|

Loss of dystrophin causes aberrant mechanotransduction in skeletal muscle fibers

Abstract: Dystrophin is a cytoskeletal protein found at the inner surface of skeletal and cardiac muscle fibers. We hypothesize that deficiency of dystrophin increases muscle compliance and causes an aberrant mechanotransduction in muscle fibers. To test this hypothesis, we measured the length-tension relationships and determined intracellular signaling leading to the activation of mitogen-activated protein (MAP) kinases in diaphragm muscle fibers from dystrophin-deficient mdx mice. Compared with controls, length-tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
135
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 59 publications
7
135
1
1
Order By: Relevance
“…[17][18][19][21][22][23] Nevertheless, these studies have generally focused on one protein rather than assessing the global changes that may precipitate or exacerbate the pathology. Moreover, they have been mainly performed in the mdx mouse, a model that most likely will exhibit species specific changes that may not be reflected in the course of the human disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][21][22][23] Nevertheless, these studies have generally focused on one protein rather than assessing the global changes that may precipitate or exacerbate the pathology. Moreover, they have been mainly performed in the mdx mouse, a model that most likely will exhibit species specific changes that may not be reflected in the course of the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Moreover, studies of the X chromosome-linked muscular dystrophy (mdx) mouse 16 revealed modulations in mitogen-activated protein kinase (MAPK) signaling cascades, as dystrophic animals exhibited increased phosphorylation of extracellular signal-regulated kinases 1 and 2 (ERK1/2) 17,18 and c-jun N-terminal kinases 1 and 2 (JNK1/2), 19 -21 and decreased phosphorylation of p38. 18 Also, the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway has been shown to be affected in the mdx mouse, with increased synthesis and phosphorylation of Akt.…”
mentioning
confidence: 99%
“…14,43,44 Another intriguing, although purely speculative, hypothesis to explain the CsA effectiveness in both DIA and EDL muscle is that the expression of functional chloride channel may be controlled by mechanosensitive mitogen-activated protein kinase (MAPK) cascades that are enhanced in dystrophin-deficient muscle fibers and also involves activation of calcineurin. 42,49,50 In fact this complex network of kinase/phosphatase pathways modulates different cellular targets either in a short term or through the modulation of gene expression, ie, by enhancing the transcription of inflammatory genes or controlling translational events of ion channels. 42,50,51 The CsA treatment did not ameliorate the alteration of calcium homeostasis that is a typical hallmark of dystrophic fibers and is worsened by exercise.…”
Section: Csa Exerts Different Effects On Functional Cellular Parametementioning
confidence: 99%
“…42,49,50 In fact this complex network of kinase/phosphatase pathways modulates different cellular targets either in a short term or through the modulation of gene expression, ie, by enhancing the transcription of inflammatory genes or controlling translational events of ion channels. 42,50,51 The CsA treatment did not ameliorate the alteration of calcium homeostasis that is a typical hallmark of dystrophic fibers and is worsened by exercise. 2,4,29 CsA per se may even lead to a further increase in calcium mobilization; 52 thus our finding leads to two main considerations: the first one is that the alteration in calcium homeostasis is rather independent on the inflammatory reaction.…”
Section: Csa Exerts Different Effects On Functional Cellular Parametementioning
confidence: 99%
“…3 Dystrophin 4 is a peripheral membrane protein of ~426 kDa important for maintenance of muscle integrity, such that its deficiency results in the structural perturbation of the plasma membrane of skeletal muscle fibers. 5 Indeed, dystrophin associates with a large multimeric complex, termed the dystrophin-glycoprotein complex (DGC), including the dystroglycan complex (a and b-dystroglycan) and the sarcoglycan complex (a, b, g, d-sarcoglycan). 6 The consequence of loss of dystrophin is the absence or the great reduction of components of the DGC, as described for skeletal muscle fibers from DMD patients and from a mouse model of DMD, named the mdx mouse.…”
Section: Introductionmentioning
confidence: 99%